No impact of anthropometric and fitness factors on speed-agility in young soccer players: is it a cognitive influence? - Giuriato, M.; Carnevale Pellino, V.; Kawczynski, A.; Talpey, S. W.; Lovecchio, N. (International Journal of Sports Physiology and Performance, 2024)
Purpose Agility in young soccer players has long been associated with physical attributes like strength, speed, and power. The aims of this study were to investigate the relationship between cognitive factors and agility performance in this unique population.